Analisis Risiko Kesehatan Lingkungan Pajanan NO₂ pada Pedagang Tetap di Terminal Brawijaya, Kabupaten Banyuwangi - Diana Agustina; Muhammad Farid Dimjati Lusno (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The increasing transportation activity in urban areas contributes significantly to air pollution, particularly through emissions containing Nitrogen Dioxide (NO₂). This reactive oxidizing gas can cause respiratory disorders and eye irritation, especially among high-risk groups such as permanent vendors working in bus terminals. This study aimed to analyze the environmental health risks of NO₂ exposure and identify related health complaints among permanent vendors at Brawijaya Bus Terminal, Banyuwangi Regency. A descriptive observational study with a cross-sectional approach was conducted and analyzed using the Environmental Health Risk Assessment (EHRA) method. Secondary data on NO₂ concentrations were obtained from the Banyuwangi Environmental Agency (average 0.00874 mg/m³), while primary data on respondent characteristics and health complaints were collected through questionnaires involving 10 permanent vendors. The results showed that the Risk Quotient (RQ) values for both realtime and lifetime exposure were below 1, indicating no significant non-carcinogenic risk. However, 60% of respondents reported coughing, 30% experienced shortness of breath, and 40–60% reported eye irritation. These findings indicate potential long-term health effects even though NO₂ levels remain below national air quality standards. Regular air quality monitoring, vehicle emission control, and health education for vendors are recommended to reduce exposure risks in transportation environments.